Capacitor voltage predictor-corrector balancing approach with single sensor for single-phase modular multilevel converter. (July 2021) - Yue, Yufei; Xu, Qianming; Guo, Peng; Chu, Xu; Shuai, Zhikang; Luo, An; Guerrero, Josep M.
Highlights: The predictor-corrector is proposed to obtain capacitor voltage with single sensor. The principle and convergence capability of the predictor-corrector is analyzed. A good convergence performance of the proposed predictor-corrector is validated. Compared simulations and experiments are tested to validate predictor-corrector. Abstract: This paper presents a predictor-corrector approach for submodule (SM) capacitor voltage measurement in single-phase modular multilevel converter (MMC). The single voltage sensor is applied to each arm for SM capacitor voltage measurement instead of using a large number of individual voltage sensors, simplifying the measurement hardware structure. With only one voltage sensor in each arm, the proposed approach utilizes measured arm voltage variation between adjacent control periods to correct the predicted capacitor voltages, improving the predictor accuracy. Additionally, the proposed approach divides the SMs into several categories in terms of their switching states variation and arm voltage level variation, and then the approach corrects the predicted capacitor voltages according to the categories, achieving the voltage-balancing of SMs. Further, the convergence capability is explained and the sensitivity against parameter perturbation and voltage unbalance condition is validated. Extensive comparison simulation and experimental tests for individual measurement, a two-step estimation algorithm, and the proposed approach are carried out. Both steady-state and transient performances are evaluated by the tests to support the feasibility and effectiveness of the proposed approach.